PENGARUH REKAYASA MEDIA VISUAL TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PAI PADA SMAN UNGGUL ACEH BESAR - Ilham, Ilham (FITRAH: International Islamic Education Journal, 2021)
This study aims to find and find the effect of visual media engineering in Islamic Religious Education learning on students' learning motivation at SMAN Unggul Aceh Besar. The variables of this study consisted of independent variables, namely: image visual media engineering (X1), graphic visual media engineering (X2), animation visual media engineering (X3) and the dependent variable, namely: student learning motivation (Y). The sampling technique used is Accidental Sampling. The number of samples in this study were 296 students. The instrument used in the questionnaire consists of 100 statements (25 statements for each variable). The data analysis technique used validity test, reliability test, data normality test, regression analysis, and coefficient of determination using SPSS 24.0 for windows program. Based on the results of the recapitulation of the questionnaire scores for the variable statement X1 (visual image media engineering) of 0.618 while the average result of the recapitulation of the questionnaire acquisition variable for the Y variable (student learning motivation) is influenced by the X1 variable (visual image media engineering) of 61.80% . The result of the coefficient of determination recapitulation of the acquisition of the questionnaire value for the statement of the variable X2 (visual graphic media engineering) is 0.846 while the coefficient of determination while the average recapitulation result of variable Y (student learning motivation) is influenced by engineering visual graphic media (X2) of 84.6% . The result of the coefficient of determination recapitulation of the acquisition of the questionnaire value for the variable statement X3 (visual animation media engineering) is 0.908. While the results of the coefficient of determination while the average results of recapitulation of variable Y (student learning motivation) are influenced by engineering visual graphic media (X3) of 90.8%. Meanwhile, to find the joint effect of variables X1, X2, X3 on variable Y, multiple regression analysis is used with the calculation results Y = 3.435 + 0.168 X1 + -0.349 X2 + 1.125 X3 obtained by the coefficient of determination that R square is 0.941 which means 94.1% motivation student learning (Y) is influenced by the engineering variable of visual image media (X1), engineering visual graphics media (X2), and engineering visual animation media (X3) while the rest is influenced by variables not examined in this study and the results of the Simultaneous Test (Statistical test). F) by using SPSS version 24.0 for windows, the significance result is obtained by the value of 0.000 < 0.05. So the hypothesis stating "there is a positive influence of image visual media engineering (X1), graphic visual media engineering (X2) and animation visual media engineering (X3) on students' learning motivation (Y)", is accepted. The findings in this study are (1) Reconstruction of the Use of Visual Media, (2) Innovation in increasing Student Learning Motivation (3) Islamic learning revolution.